Do leadership and work environment affect employee performance? Case study in Mustikasari Village Bekasi City - Dian Ayu Anggraeni Kusumadewi (Peneliti.net, 2022)
This study aims to determine and analyze how much influence leadership and work environment have on employee performance in Mustikasari Village, Bekasi City. This study uses quantitative research which is a study that aims to explain the relationship between two or more variables with a sample of 35 respondents. Data collection methods used are questionnaires, documentation and literature studies. The data processing technique uses the help of the IBM SPSS version 26.0 application program so as to get the test results from the instrument test, classical assumption test, multiple linear regression test, coefficient of determination test and hypothesis testing (t test and f test). The results showed that leadership and work environment had a positive and significant influence on employee performance. Based on the test results the coefficient of determination is 49.2% while the remaining 50.8% is influenced by other variables that are not included in this research model. Based on the results of the t-test (partial) and the results of the f-test (simultaneous) indicate that there is a significant influence partially or simultaneously between the variables of leadership and work environment on employee performance.